2020
DOI: 10.1002/ejoc.202000288
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylation of Alkenyl Boronic Acids and Alkenyl Boronic Acid Pinacol Esters with CO2 Catalyzed by Cuprous Halide

Abstract: A cuprous halide catalysed carboxylation of alkenyl boronic acids and alkenyl boronic acid pinacol esters under CO 2 , affording the corresponding α, -unsaturated carboxylic acids in good yield, has been developed. The potassium (E)- [a] . The current research interests of his group include CO 2 utilization in organic synthesis, organic electrochemistry, and modification of semiconductor oxides for energy and resource utilization.Scheme 2. The reaction of (E)-styrylboronic acid 1a, (E)-4,4,5,5-tetramethyl-2-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Compared to the previous studies, they reported the use of alkenyl boric acids and alkenyl potassium trifluoroborates instead of alkenyl boronic acid esters as the starting materials for carboxylation reactions. [256][257][258][259][260][261][262][263][264][265] By this strategy, a,b-unsaturated carboxylic acids were synthesized, which have numerous applications in the pharmaceutical industry or as intermediates in organic synthesis. 250 After the optimizations, it was found that styryl boronic acid (270) reacted with CO 2 to form cinnamic acid (271) in 92% yield by using CuCl and KOMe in DMA at 70 1C for 24 h (Scheme 43).…”
Section: Copper-catalyzed Carboxylationmentioning
confidence: 99%
“…Compared to the previous studies, they reported the use of alkenyl boric acids and alkenyl potassium trifluoroborates instead of alkenyl boronic acid esters as the starting materials for carboxylation reactions. [256][257][258][259][260][261][262][263][264][265] By this strategy, a,b-unsaturated carboxylic acids were synthesized, which have numerous applications in the pharmaceutical industry or as intermediates in organic synthesis. 250 After the optimizations, it was found that styryl boronic acid (270) reacted with CO 2 to form cinnamic acid (271) in 92% yield by using CuCl and KOMe in DMA at 70 1C for 24 h (Scheme 43).…”
Section: Copper-catalyzed Carboxylationmentioning
confidence: 99%
“…The scope of copper‐catalyzed carboxylation of the organoboron substrates was further expanded by Mo and co‐workers, who utilized alkenyl boric acids and alkenyl boronic acid pinacol esters as reactive partners with CO 2 under copper catalysis (Scheme 7). [19] The simple CuCl was used as catalyst, enabling the production of α,β‐unsaturated carboxylic acids in moderate to high yields. The potassium (E)‐trifluoro(styryl)borate also served as a suitable substrate under the current catalytic system.…”
Section: Copper‐catalyzed Carboxylation Of Organic Halides and Their ...mentioning
confidence: 99%